Inhibition of unfolded protein response prevents post‐anesthesia neuronal hyperactivity and synapse loss in aged mice. Issue 4 (17th March 2022) - Chen, Kai; Hu, Qiuping; Gupta, Riya; Stephens, Jessie; Xie, Zhongcong; Yang, Guang
Abstract: Delirium is the most common postoperative complication in older patients after prolonged anesthesia and surgery and is associated with accelerated cognitive decline and dementia. The neuronal pathogenesis of postoperative delirium is largely unknown. The unfolded protein response (UPR) is an adaptive reaction of cells to perturbations in endoplasmic reticulum function. Dysregulation of UPR has been implicated in a variety of diseases including Alzheimer's disease and related dementias. However, whether UPR plays a role in anesthesia‐induced cognitive impairment remains unexplored. By performing in vivo calcium imaging in the mouse frontal cortex, we showed that exposure of aged mice to the inhalational anesthetic sevoflurane for 2 hours resulted in a marked elevation of neuronal activity during recovery, which lasted for at least 24 hours after the end of exposure. Concomitantly, sevoflurane anesthesia caused a prolonged increase in phosphorylation of PERK and eIF2α, the markers of UPR activation. Genetic deletion or pharmacological inhibition of PERK prevented neuronal hyperactivity and memory impairment induced by sevoflurane. Moreover, we showed that PERK suppression also reversed various molecular and synaptic changes induced by sevoflurane anesthesia, including alterations of synaptic NMDA receptors, tau protein phosphorylation, and dendritic spine loss. Together, these findings suggest that sevoflurane anesthesia causes abnormal UPR in the aged brain, which contributes to neuronal hyperactivity, synapse loss and cognitive decline in aged mice. Abstract : Older individuals are particularly susceptible to postoperative brain dysfunction, but the mechanism underlying anesthesia‐induced cognitive decline is not yet clear. This study shows that exposure of aged mice to anesthesia causes an abnormal increase in neuronal activity in the frontal cortex where dysregulation of unfolded protein response (UPR) is also observed. Inhibition of PERK, a key component of UPR, prevents anesthesia‐induced neuronal hyperactivity, synapse loss, and memory impairment.